Shifting Ideology and Religiopolitical Behavior of Conservative and Radical Islam in Contemporary Indonesia - Anwar, M. Syafi'i (Religió Jurnal Studi Agama-agama, 2025)
Indonesians have been known to be predominantly moderate Muslims to the present day. However, the developments show the rise of the Conservative and Radical Islam (CRI) movement that challenged moderate Islam’s dominance for the last two decades. Yet, there is a recent ideological shift among the groups towards a more inclusive standpoint. This research aims to provide a critical account of the ideological shift and religiopolitical behavior of CRI groups. This research employed a qualitative approach, in which the data were collected through a literature review and interviews with CRI figures. The study discovers that the sociohistorical origins, ideology, and religiopolitical behavior of CRI in Indonesia are rooted in the spread of Salafism and Wahhabism in the Middle East and East Africa. It also reveals that the rise of CRI movements in Indonesia is related to the development of political Islam since the rise of the reformasi era in 1998. Moreover, the study also finds that some CRI actors tend to lower their exclusive and radical approach to some extent as they tend to be more realistic toward current religious and political issues.